Genetic variability of the ABCC2 gene and clinical outcomes in pancreatic cancer patients - Gentiluomo, Manuel; Tjaden, Christin; Strobel, Oliver; Neoptolemos, John P.; Hackert, Thilo (Carcinogenesis, 2019)
We investigated the possible association between single nucleotide polymorphisms (SNPs) in the ABCC2 gene and overall survival (OS) in pancreatic ductal adenoca
Gesehen am 11.12.2019